ANALISIS PENGARUH PENGHASILAN PEMBUDIDAYA RUMPUT LAUT (E. COTTONI) DI DESA TANAMANANG KECAMATAN PAHUNGAN LODU KABUPATEN SUMBA TIMUR - Denisius Umbu Pati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Seaweed is one of the potential fishery commodities to be cultivated. Seaweed has multiple functions in various industries such as food, beauty, pharmaceutical, textile and agriculture industries. This study aims to analyze the effect of income for Sakol (E. cottoni) Seaweed Cultivators in Plantang Village, Pahungan Lodu District, East Sumba Regency. The type of research conducted in this research is an analytical survey with a cross sectional study design. The research location is in Plantang Village, Pahunga Lodu District, East Sumba Regency. The population in this study were 145 seaweed farmers. The sample in this study was 102 seaweed cultivators. The results of the univariate analysis showed that the income of seaweed cultivators according to household needs was 41 (40.20%) cultivators and the income of seaweed cultivators who were not suitable was 61 (59.80%) cultivators. The results of the bivariate analysis showed that there was a very significant effect between the number of hours worked (p = 0.038) and the capital of the farmer (p = 0.041) and the income of the seaweed farmers, while the results showed that there was no effect between the level of education of the farmers (p = 0.107). with seaweed farming income. The conclusion of this study is that there is a very significant effect between the number of hours worked and the capital of the farmer and the income of seaweed cultivation.